Individual anatomical variability of the skull`s facial section considering gender and craniotype based on computed tomography data - Sosonna, L.; Ohurtsov, O.; Piriatinska, N.; Vdovitchenko, V.; Seleznova, R.; Kolba, O.; Gryzodub, D.; Rozhkovа, O.; Shevtsov, O. (Tbilisi : Nʹi︠u︡-Ĭork : Assot︠s︡iat︠s︡ii︠a︡ delovoĭ pressy Gruzii ; International Academy of Science, Education, Industry & Arts, 2024)
The study of individual anatomical variability has long attracted attention, with this topic being widely covered in the works of both domestic and foreign scientists. The aim of our work is to study the individual anatomical variability of the facial section of the skull, taking into account gender and craniotype, based on computed tomography data. Material and Methods. The material for our study consisted of 80 results from computed tomography (CT) scans of the human head, without any existing pathologies of the bone tissue. Results. Brachycrania was established in males with a cranial index ranging from 80.6 to 92.4 (with x̄ = 86.68, σ = 3.20, and mx̄ = 0.91), and in females from 80.2 to 88.3 (with x̄ = 84.32, σ = 2.81, and mx̄ = 0.77). Similarly, mesocrania was confirmed by our data, with males showing a range from 76.8 to 79.2 (with x̄ = 77.93, σ = 1.72, and mx̄ = 0.68), and females from 75.6 to 79.1 (with x̄ = 77.12, σ = 1.74, and mx̄ = 0.59). Dolichocrania presented a variability range of cranial index values in adult males from 71.8 to 74.6 (with x̄ = 73.80, σ = 1.52, and mx̄ = 0.63), and in females from 72.2 to 73.9 (with x̄ = 72.67, σ = 1.48, and mx̄ = 0.59). Conclusions. The individual anatomical variability of the facial section of the skull, taking into account gender and craniotype, based on computed tomography data was detected. Cranial profile characteristics of the facial skeleton are dependent on both gender and on the existing craniotype. We were able to establish clear differences between male and female skulls, particularly in terms of overall linear dimensions, the shapes of lateral polygons, and profilograms. A clear description of the brachycranial, mesocranial, and dolichocranial craniotypes was obtained, along with their relationships to other existing skull types.
Funding: This research received no external funding. Conflict of interest statement: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.
Keywords: MEDICINE; cranial index; computer tomography; height-length index; height-breadth index